Unpacking the Aid-Growth Nexus in Nepal: Evidence from Two Decades of Time-Series Data - Adhikari, Govinda (Chaturbhujeshwar Academic Journal, 2025)
This study examines the relationship between foreign aid utilization and economic growth in Nepal from 2003/04 to 2023/24, grounded in the Two-Gap Model as a theoretical framework. Using time-series data, it assesses whether actual disbursed foreign aid has contributed to the economic performance of Nepal. Although foreign aid has remained a significant source of development financing, its share in the national budget has steadily declined over the study period. Statistical analyses, including Pearson correlation and simple linear regression, reveal a very weak positive relationship (r ≈ 0.039) between aid utilization and economic growth. These findings suggest that foreign aid alone has not consistently driven economic growth in Nepal. This may be due to broader structural conditions such as institutional capacity, governance quality, and policy alignment. The study highlights the need for further research on sectoral impacts, the role of political stability and donor coordination, and the underlying causes of fluctuating growth patterns of the country. Overall, while foreign aid continues to play an important role in development financing, it must be supported by domestic reforms to ensure its effectiveness in promoting sustainable and inclusive economic growth. The significance of this study lies in its focus on actual aid utilization and its policy-oriented insights for improving aid effectiveness in the Nepalese context.